DIPG-32. CLINICALLY RELEVANT AND MINIMALLY INVASIVE TUMOR SURVEILLANCE IN PEDIATRIC GLIOMAS USING LIQUID BIOME. Issue 2 (22nd June 2018) - Panditharatna, Eshini; Kilburn, Lindsay; Aboian, Mariam; Kambhampati, Madhuri; Gordish-Dressman, Heather; Magge, Suresh; Gupta, Nalin; Myseros, John; Hwang, Eugene; Crawford, John; Warren, Kathy; Resnick, Adam; et al.
Abstract: Pediatric diffuse midline glioma (MLG) constitutes the deadliest childhood CNS cancers. Due to the sensitive anatomical location, lack of surgical access to the tumor has hindered molecularly informed clinical interventions; thus, there is a dire need for the development of a sensitive and accurate approach for mapping tumor DNA fingerprints and monitoring tumor response to therapy. Liquid biopsy is emerging as a minimally invasive method for detecting circulating tumor DNA (ctDNA) in patients' biofluid. To use liquid biopsy for mapping genomic mutations in pediatric brain tumors, we designed, optimized, and validated probes, and then showed their sensitivity and specificity for clinical assessment of children diagnosed with MLGs. Specifically, we demonstrated the feasibility of generating multiplex assays for detection of multiple driver mutations in patients' biofluid. Tumor ctDNA was detected in cyst fluid (n=1), cerebrospinal fluid (CSF, n=30) and plasma (n=77), representing 48 subjects admitted or enrolled in a clinical trial. We show that while both CSF and plasma contain ctDNA, CSF tended to be a more enriched medium for tumor-associated ctDNA. Furthermore, we have detected H3K27M in ctDNA of plasma samples in xenograft models of DIPG. Finally, we show that ctDNA analysis closely agree with tumor response, often providing similar trends compared to MR imaging. Our data are the first to indicate the clinical utility of ctDNA for monitoring tumor response, and provide a molecularly-based rapid and sensitive approach for detection and longitudinal survey of childhood CNS tumors.